O17 When's best to text? optimum timing of sms appointment reminders. (18th May 2015) - Williams, Caroline; Gregory, Luke; Apoola, Ade; Wood, Hayley
Abstract : Background/introduction: Throughout healthcare settings 'did not attend' (DNA) rates impact heavily on service efficacy and are estimated to cost the NHS £600 m per year. Short message service (SMS) texts have been shown to reduce the DNA rates amongst Sexual Health patients. Aim(s)/objectives: The aim of this project was to assess the optimum timing of SMS appointment reminders and its impact on the non-attendance rates in our HIV and Sexual Health service. Methods: For three consecutive four week periods between 30/12/2013 and 06/04/2014, in addition to the routine 'on the day' SMS reminder an extra reminder was sent 1, 2 or 3 days prior to patient appointments. Data was collected concerning patient attendances during these periods for pre-booked appointments for HIV and Sexual Health patients. Statistical significance was calculated using Fisher's Exact test and Pearson's correlation coefficient as appropriate. Results: Attendance was monitored for 1, 271, 1, 215 and 1, 264 patients in each 4 week group respectively. Amongst HIV patients, DNA rates fell as the time increased between the appointment and sending the extra SMS reminder. For Sexual Health patients, DNA rates fell as the time was decreased between the appointment and the extra SMS reminder. For both patient groups the gradient of this fall was statistically significant. Discussion/conclusion: This small project has demonstrated the optimum timing of SMS reminders appears different for HIV and Sexual Health patients. HIV patients had lower DNA rates when texted further from the appointment time, whereas Sexual Health patients DNA'd less often if texted nearer to their appointment. Further work is needed confirm the generalisability of our findings and reasons underpinning them.